Структурні та генетичні особливості літичного бактеріофага Lw1, нового представника псевдо Т-парних фагів - Кушкіна, А.І. (Фактори експериментальної еволюції організмів, 2015)
Aims. Bacteriophages are diverse group of bacterial parasites which have complex, but insuffi cient systematics. RB43-related
bacteriophages have a specifi c genome type that clearly distinguishes them from other T4-like viruses. The main aim was to
identify new Myoviridae phage Lw1 isolated as an E. coli BL21 (DE3) contaminant. Methods. Microbiological, biophysical,
molecular biology and bioinformatic methods were used to reach the aims. Results. Here we present main characteristics and
complete genome sequence of a new lytic phage Lw1 which shares RB43-like genome organization, but it does not contain
putative AP2-domain endonuclease genes. Conclusions. By genomic organization phage Lw1 belongs to subgroup of RB43-
like pseudo T-even phages. Although the Lw1 genome does contain one T4-like phage endonuclease of the MobE family,
there is a lack of AP2-domain-containing endonucleases, and the relative paucity of mobile elements indicates either recent
loss events or the presence of limited sites for viable insertion in the genome compared to some other RB43-like phages.
Keywords: T4-like phages, identifi cation, morphology, structural proteins, DNA pattern, genome organization, phagespecifi c nucleases, gene drift.